2014
DOI: 10.1021/jo500813n
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of a Smoothened Cholesterol: 18,19-Di-nor-cholesterol

Abstract: Herein, we report the first synthesis of a demethylated form of cholesterol (18,19-di-nor-cholesterol), in which the C18 and C19 methyl groups of the β-face were eliminated. Recent molecular simulations modeling 18,19-di-nor-cholesterol have suggested that cholesterol’s opposing rough β-face and smooth α-face play necessary roles in cholesterol’s membrane condensing abilities and, additionally, that specific facial preferences are displayed as cholesterol interacts with different neighboring lipids and transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Following the removal of the silyl group under mild acidic conditions, the free benzylic −OH group was then acylated using three different N-alloc protected amino acids giving the key precursor (29) to study the 15-membered ring formation by a ring closing metathesis stitching approach. As in the previous study, this reaction also worked-well, and in all the three cases, macrocyclic ring was obtained (see 30). The reaction appears to independent of the stereochemistry of -O-acryloyl group at C-2 and with the choice of different amino acid moieties utilized for acylation at C-9.…”
Section: Acs Combinatorial Sciencesupporting
confidence: 77%
“…Following the removal of the silyl group under mild acidic conditions, the free benzylic −OH group was then acylated using three different N-alloc protected amino acids giving the key precursor (29) to study the 15-membered ring formation by a ring closing metathesis stitching approach. As in the previous study, this reaction also worked-well, and in all the three cases, macrocyclic ring was obtained (see 30). The reaction appears to independent of the stereochemistry of -O-acryloyl group at C-2 and with the choice of different amino acid moieties utilized for acylation at C-9.…”
Section: Acs Combinatorial Sciencesupporting
confidence: 77%
“…This difference might explain why the domain-forming capabilities of cholesterol and DMchol are different despite having similar local ordering abilities. Though a synthesis route for DMchol was very recently discovered 62 , its effects on membrane phase behaviour have not been studied experimentally. However, studies on lanosterol — a cholesterol analogue with two rough faces— suggested that it has a weaker ordering effect compared to cholesterol 63 and that the liquid–liquid coexistence region was not present in lipid–lanosterol mixtures 64 , in agreement with our results, further supporting the important role of cholesterol asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…A second group of synthetic cholesterol analogues is derived by modifying the functional groups of cholesterol, with the purpose of investigating the important functions of cholesterol structure. These cholesterol derivatives include enantiomeric cholesterol, 188 epicholesterol, 189 sterols without methyl groups on the rings, 190193 and sterols with a modified side chain. 194…”
Section: Biomembranes As the Target Of Simulations: Native Membranes mentioning
confidence: 99%